Comparing the Effects of Mineral Trioxide Aggregate and Calcium Enriched Mixture on Neuronal Cells Using an Electrophysiological Approach - Abbasipour, Fatemeh; Akheshteh, Vahid; Rastqar, Ali; Khalilkhani, Habib; Asgari, Saeed; Janahmadi, Mahyar (Iranian Endodontic Journal, 2012)
Introduction: The main goal of this ex vivo study was to assess and compare the cellular and electrophysiological effects of two dental biomaterials, white mineral trioxide aggregate (WMTA) and calcium enriched mixture (CEM) cement, on neuronal cell excitability and electrical properties. Materials and Methods: A conventional intracellular current clamp technique was used to study the cellular effects of WMTA and CEM on the excitability, firing and the shape of action potential of neuronal soma membrane of F1 nerve cells. The dental biomaterials were prepared according to the manufacturers’ directions and were applied to the bathing media and 0.05 mL of total mixture of each dental material at a distance of 3 mm from the cells. Results: Findings indicated that exposure to both dental biomaterials shifted the irregular high frequency firing type observed in control conditions to a more regular low frequency firing pattern. Neuronal exposure to WMTA, but not CEM, significantly hyperpolarized the cell resting membrane potential. Both treatments significantly influenced the duration and the amplitude of action potentials. Extracellular application of either CEM or WMTA caused a significant increase in the after hyperpolarization (AHP) amplitude and AHP area, but the potentiating effect of WMTA was more effective than CEM. <span style="font-size: 11pt; color: black; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Conclusion: Treatment with WMTA or CEM resulted in a profound alteration in the firing behaviour of F1 cells and changed the AP characteristics. Both dental biomaterials reduced the neuronal activity possibly through enhancement of K+ outward current. This may possibly explain the positive mechanisms of these biomaterials in regenerative endodontics, though further research is needed for such a conclusion.